Parental attachment, coping efficacy and antisocial behavior among adolescents from divorced family in Selangor, Malaysia - Yaacob, Siti Nor; Idris, Farah Azimah; Gan, Su Wan (Macrothink Institute, 2015)
The main purpose of this study was to determine the relationships between parental attachment, coping efficacy and antisocial behavior among adolescents from divorced families. Respondents were 170 secondary school students aged 13 to 17, selected using purposive sampling technique. Self-administered questionnaire was used in data collection. Adolescents’ attachment with parent was assessed with Parent Attachment subscale from Inventory of Parent and Peer Attachment (IPPA). Coping Self-Efficacy Scale (CSES) and Subtypes of Antisocial Behavior Questionnaire (STAB) were used to measure adolescents’ coping efficacy and antisocial behavior respectively. Correlation analysis showed that mother attachment (r = -.219, p < .01) and coping efficacy (r = -.365, p < .001) had significant negative correlation with antisocial behavior. Coping efficacy fully mediated the relationship between mother attachment and antisocial behavior (Z = -3.197, p < .001). Intervention or prevention programs should target both mothers and children from divorced families.